Short-Term Outcomes of Refractory Diabetic Macular Edema Switch From Ranibizumab to Dexamethasone Implant and the Influential Factors: A Retrospective Real World Experience - Ning-Yi Hsia; Chun-Ju Lin; Chun-Ju Lin; Chun-Ju Lin; Huan-Sheng Chen; Cheng-Hsien Chang; Cheng-Hsien Chang; Cheng-Hsien Chang; Henry Bair; Henry Bair; Chun-Ting Lai; Jane-Ming Lin; et al. (Frontiers in Medicine, 2021)
Introduction: To evaluate the effectiveness and safety of intravitreal dexamethasone (DEX) implants in refractory diabetic macular edema (DME) treated by intravitreal ranibizumab.Materials and Methods: We retrospectively analyzed DME patients who received DEX implant treatment after being refractory to at least 3 monthly intravitreal ranibizumab injections. The main outcomes were best-corrected visual acuity (BCVA), central retinal thickness (CRT), and intraocular pressure (IOP).Results: Twenty-nine eyes of 26 patients who had previously received an average of 8.1 ± 4.4 ranibizumab injections were included. Patients received between one and three DEX implants during 12.4 ± 7.4 months of follow-up. The mean final CRT significantly decreased from 384.4 ± 114.4 μm at baseline to 323.9 ± 77.7 μm (p = 0.0249). The mean final BCVA was 51.4 ± 21.3 letters, which was not significant compared to baseline (44.9 ± 30.2 letters, p = 0.1149). Mean IOP did not increase significantly. All patients tolerated the treatment well without serious adverse events. Higher baseline CRT and worse BCVA correlated with better therapeutic responses.Conclusion: Switching to DEX implant is feasible and safe for treating patients of DME refractory to intravitreal ranibizumab in real world. Further larger-scale or multicenter studies would be conducted to explore different DEX treatment strategies for DME, such as first-line or early switch therapy, for better BCVA improvement.